PENERAPAN SMK3 DI LINGKUNGAN KERJA MANUFAKTUR PRODUK MAKANAN DAN MINUMAN - Marlina, Lala; Rizal, Reda (Bina Teknika, 2016)
To ensure the safety and health of workers or others who are in the workplace, including the source of production, production processes, and working in safe environment, that showing the application of Occupational Safety and Health Management System (SMK3). The main purpose of application of SMK3 is to giving protection for the workers. Because, workers are assets to be maintained and guarded their safety. The purpose of this study is to determine the extent to which description of the application Government of Regulation Number 50 in 2012 about SMK3 at Food-Beverage Manufacture in 2015. This research use qualitative method and case study design. The object of this study about SMK3 in Food-Beverage Manufacture. The result of study showed that Food-Beverage Manufacture 89% has completed SMK3 Government of Regulation in which consists: (i) the company has not had a person in charge K3 Certificate valid for every worker who was given the responsibility, (ii) don’t yet have procedures regarding the purchase of equipment or materials production, (iii) not create a new certificate upon expiration crane certificate, (iv) yet have a tagging system for the equipment that is no longer safe to use or are not used, (v) has not tested the emergency alarm system (e.g. sprinkler), (vi) have not done the work environment measurement (ergonomics and psychology), (vii) have not had the procedure inspection and assessment of occupational diseases.